Assessment of cortisol in sheep wool during shearing: progress toward an animal welfare biomarker in La PampaDetermination of cortisol in sheep wool as a retrospective indicator of animal welfare during shearing in La Pampa: Assessment of cortisol in sheep wool during shearing: progress toward an animal welfare biomarker in La PampaDetermination of cortisol in sheep wool as a retrospective indicator of animal welfare during shearing in La Pampa (Veterinary Science, 2026)
Animal welfare in sheep production systems is a key component for maintaining competitive and sustainable practices. Cortisol, a hormone linked to the stress response, is frequently measured in blood, a matrix that reflects acute situations. Wool, in contrast, allows recovery of information regarding exposure to stress over time. The aim of this study was to evaluate whether measuring cortisol in wool can act as a retrospective indicator of stress and to compare it with plasma levels. The study was conducted in two farms in northern La Pampa, where thirty-eight adult ewes were sampled. One month after shearing, wool samples were collected and sectioned into base, the portion that does not reflect the shearing event, and tip, which does incorporate its effect. Preliminary results from the 2023 shearing showed an average plasma cortisol value of 208.12 nmol/L. In wool, the mean of the base segment was 6.72 pg/mg, while the tip segment reached 13.45 pg/mg. The difference between them was significant (p < 0.001) and showed a large effect size (ES = 1.72). No correlation wasobserved between plasma cortisol and wool values (r = –0.14; p = 0.41). These findings indicate that fiber allows retrospective recovery of stress information associated with shearing and may serve as a non-invasive biomarker for real production systems. Analysis of the 2024 samples will help consolidate these values and advance their standardization.